Students’ perception of authentic assessment in higher education: Exploring the relationship between assessment preference and motivation in higher education - Stephanie Baines; Satyam Chauhan; Pauldy C. J. Otermans (Cogent Education)
There is an increasing shift from traditional knowledge-testing exams to more effective learning-oriented assessments in Higher Education. There is limited evidence examining students’ perception of the authenticity of different Higher Education assessments predicted by intrinsic, extrinsic, and amotivation levels. Ninety-six young adults (19-49 years; 68 females) completed an online survey to investigate the role of motivation in preference ratings for 25 different assessments. Results showed that students only had a slight preference for certain assessments. In more detail, they had a significantly higher preference for poster submission predicted via intrinsic motivation, poster presentation predicted via intrinsic (to know) and extrinsic (introjected) motivation, multiple choice question exam (within a set framework), predicted via extrinsic (identified and introjected) motivation and amotivation, essay exam predicted via amotivation, and lab report predicted via extrinsic (introjected) motivation and amotivation. Therefore, alongside the facilitation of knowledge and understanding, assessments in Higher Education should be designed to foster interest and passion to conceptual learn and enjoy the content.